Three-phase Self-Excited Induction Generator Operating as Single-phase Induction Generator using Static VAR Compensator - Sawat Yukhalang; Theppanom Sopapirm; Vijit Kinnares (My University, 2023)
This paper proposes a performance analysis of using a static volt-amp-reactive (VAR) compensator for a three-phase self-excited induction generator (SEIG) operating as a single-phase induction generator. The study proposes appropriate capacitor for building up voltage supplying power to load with static VAR for regulating terminal voltage. The simulation model is analyzed by using MATLAB/Simulink under various conditions such as reactive power supplied, dynamic response, steady state, building up voltage for startup, linear load, non-linear load and harmonics in system. From the study (based on the study, the findings revealed it is found) that using the static VAR compensator connected in parallel with loads for supplying reactive power to the load systems is needed for maintaining terminal voltage.
Keywords: Microgrid Control and Optimization; Multilevel Inverters and Converters; Wind Turbine Control Systems